2014
DOI: 10.1371/journal.pone.0112787
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Disease Susceptibility and Sexual Dimorphism in the Heterozygous Knockout of Cyp51 from Cholesterol Synthesis

Abstract: We examined the genotype-phenotype interactions of Cyp51+/− mice carrying one functional allele of lanosterol 14α-demethylase from cholesterol biosynthesis. No distinct developmental or morphological abnormalities were observed by routine visual inspection of Cyp51+/− and Cyp51+/+ mice and fertility was similar. We further collected a large data-set from female and male Cyp51+/− mice and controls fed for 16 weeks with three diets and applied linear regression modeling. We used 3 predictor variables (genotype, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…TC in women was significantly higher than in men in our study. Previous research highlighted a difference between males and females in the causes of liver disease, with TC synthesis representing a key point of gender difference [27]. In addition, γ-GTP values of all samples were increased, with those in men significantly higher than those in women.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…TC in women was significantly higher than in men in our study. Previous research highlighted a difference between males and females in the causes of liver disease, with TC synthesis representing a key point of gender difference [27]. In addition, γ-GTP values of all samples were increased, with those in men significantly higher than those in women.…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…3) likely due to cholesterol compensation during the initial 3-week nursing period. The switch to standard laboratory chow lacking cholesterol27 raises the need for its endogenous synthesis. As this is disrupted in the knockout livers, the result is a fall in plasma and liver cholesterol at 6 weeks that is remedied at later ages, and alterations of sterol metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Cyp51 flox/flox ( Cyp51 +/+ ) and heterozygous Cyp51 -/flox ( Cyp51 +/− ) mice were used as controls27. Mice were euthanized at different time points during development – 0, 3, 6, 9 and 19 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Heterozygous knockout Cyp51a1 +/− mice are developmentally and morphologically normal and fertile; however, when challenged with high lipid diet, the response revealed a hidden susceptibility to detrimental effects of the diet (Lewinska et al, 2014). Studies in mice also revealed gender biased consequences of mutations in Cyp51a1 (Lorbek et al, 2013;Lewinska et al, 2014;Urlep et al, 2017). Consequences of CYP51A1 heterozygosity in humans need yet to be studied.…”
Section: Introductionmentioning
confidence: 99%